Fabrication of TiO2/ZnO nanocomposites for solar energy driven photocatalysis. (April 2017) - Prasannalakshmi, P.; Shanmugam, N.
Abstract: The facile sol-gel method was suggested to prepare the TiO2 /ZnO photocatalysts. For that, the nanocomposites of TiO2 /ZnO were prepared with different amounts of zinc and oxide precursors. The prepared products were characterised by XRD, FT-Raman, UV–vis DRS, TEM, EDX, BET, and EIS techniques. The photocatalytic response of TiO2 /ZnO nanocomposites was analysed for the degradation of the organic dyes brilliant green (BG), and methylene blue (MB) under solar light irradiation. As an outcome of increased surface area, rod-like morphology, low charge transfer resistance, and reduced band gap the composite of TiO2 /ZnO with an optimum level of zinc (0.25 M) and sulphur (0.5 M) contents showed enhanced photocatalytic activity in degrading the dyes BG and MB.